Solidarity between parents and their adult children in Europe - Fokkema, Tineke (NiDi rapport, 2008)
At present, our knowledge of the current state of solidarity between parents and their adult children in Europe is limited. Insight into contemporary intergenerational solidarity is not only important for the well-being of individuals but is also of great interest to policy makers. Patterns of intergenerational solidarity are not only affected by social policies and services but also reveal a number of important social policy issues and dilemmas. Will encouraging labour force participation among women and older workers mean they have less time to care for their dependents? Should formal care s.